Nano-scale precipitates: The key to high strength and high conductivity in Al alloy wire. (15th October 2017) - Hou, J.P.; Wang, Q.; Zhang, Z.J.; Tian, Y.Z.; Wu, X.M.; Yang, H.J.; Li, X.W.; Zhang, Z.F.
Abstract: Outstanding mechanical and conductive properties are vital to Al alloys used as overhead conductors. However, high strength and high electrical conductivity are usually mutually exclusive in metallic materials. In this study, we present a novel method to achieve high strength and high conductivity in an Al-Mg-Si conductor. Numerous dispersive nano-scale precipitates were obtained using an artificial aging treatment for a 6201RE Al alloy conductor. The precipitation of the alloying elements in the form of nano-scale precipitates is determined to play a strengthening role, decreasing the concentration of alloying elements in the matrix and reduce lattice distortion such that high strength (352.3 MPa) and high electrical conductivity (56.0% IACS) are achieved simultaneously in a 6201RE Al alloy. High strength and enhanced electrical conductivity could be achieved by introducing the nano-scale precipitates in the Al alloy. Finally, the strengthening mechanisms and the electrical conductivity induced by the nano-scale precipitates were discussed. Graphical abstract: Highlights: Simultaneous increase in strength and electrical conductivity of an Al-Mg-Si alloy conductor is achieved by a novel method. Numerous dispersive nano-scale (radius: 1.3 nm) precipitates are formed in the Al alloy conductor. The properties of the conductor in the present work are outstanding compared with those of the other Al-Mg-Si conductors.